Probiotic Biotechnology Innovation in Tiger Grouper Aquaculture and Its Implications for Business Economic Performance - Ratri, Kartika Chayaning; Satyantini, Woro Hastuti; Pramono, Heru (Amkop Management Accounting Review (AMAR), 2026)
The development of aquaculture technology has become an important strategy in increasing fish production while maintaining environmental sustainability. One of the innovations increasingly applied in aquaculture systems is the use of probiotics, which function to improve fish health, enhance water quality, and increase cultivation efficiency. Tiger grouper (Epinephelus fuscoguttatus) is a high-value marine commodity with significant economic potential; however, its cultivation still faces several challenges, including disease outbreaks, low feed efficiency, and unstable environmental conditions. Therefore, the application of probiotic biotechnology is considered a promising approach to address these challenges. This study employed a literature review method by analyzing various international scientific publications related to the application of probiotics in aquaculture systems. The selected literature focused on three main aspects: the application of probiotic biotechnology in tiger grouper cultivation systems, the effect of probiotics on production performance, and the economic implications of probiotic use in aquaculture businesses. The results of the literature synthesis indicate that probiotics play a significant role in improving microbial balance in both the digestive system of fish and the rearing environment. The application of probiotics has been reported to enhance fish growth rate, increase survival rate, and improve feed utilization efficiency. In addition, probiotics contribute to maintaining water quality by reducing harmful compounds such as ammonia and organic waste in aquaculture systems. Overall, the findings highlight that probiotic biotechnology innovation not only improves the biological and technical performance of tiger grouper cultivation but also provides economic benefits through increased productivity, reduced operational costs, and improved product quality. Therefore, probiotic application can be considered a strategic approach to support sustainable and economically viable aquaculture development.